Pulmonary Hamartoma: a Single-Center Analysis of 142 Cases - P. V. Gavrilov; S. S. Suvorova; U. A. Smolnikova; A. D. Ushkov (Вестник рентгенологии и радиологии, 2024)
Background. Gamartoma occupies a special place among solitary lung masses not requiring active surgical tactics: structural heterogeneity due to inclusions of fat density and calcinates presents an opportunity to identify pathognomonic computed tomographic (CT) signs. However, their absence in conjunction with CT picture inherent in malignant neoplasms can cause biopsies and surgical interventions that are not necessary according to the results of histologic examination.Objective: to perform a cohort retrospective analysis of pulmonary hamartoma CT semiotics.Маterial and methods. We analyzed 142 cases of lung hamartomas detected at the Saint Petersburg Research Institute of Phthisiopulmonology from 2013 to 2023, confirmed histologically or with a follow-up period of more than 600 days, without endobronchial location and other foci/formations in the lungs, without contrast enhancement evaluation.Results. The results of data statistical analysis of patients with pulmonary hamartoma with distribution by gender and age were described. The occurrence rate was established for such hamartoma CT features as mass type, contour features, changes in the surrounding lung tissue, the largest diameter, density, calcination type with examples on CT images. Localizations of hamartomas in relation to the lung, its lobes and segments were considered. Four hamartoma clusters depending on fat and calcination combination in the structure were identified and illustrated. The size distribution of hamartomas from each cluster within the given ranges was also presented.Conclusion. Lung hamartomas are solid-type masses without preferential localization in lung segments, with the possibility of detection at any age. In a significant proportion of cases (43.7%) hamartomas did not have any structural features, which allow, according to CT data, to convincingly classify them as benign masses and avoid surgical resection. Only in 12% of cases hamartomas had structural changes considered highly pathognomonic for their classification as benign masses.